Five Decades of Distortions to Agricultural Incentives - Anderson, Kym (World Bank, Washington, DC, 2017)
This chapter begins with a brief summary of the long history of national distortions to agricultural markets. It then outlines the methodology used to generate annual indicators of the extent of government interventions in markets, details of which are provided in Anderson and appendix A. A description of the economies under study and their economic growth and structural changes over recent decades is then briefly presented as a preface to the main section of the chapter, in which the nominal rates of assistance and consumer tax equivalents (NRA and CTE) estimates are summarized across regions and over the decades since the 1950s. These estimates are discussed in far more detail in the regional chapters that follow. A summary is also provided of an additional set of indicators of agricultural price distortions presented in chapter eleven that are based on the trade restrictiveness index first developed by Anderson and Neary (2005). In chapter twelve the focus shifts from countries to commodities, and all the various distortion indicators are used to provide a sense of how distorted are each of the key farm commodity markets globally. Then chapter thirteen uses the study's NRA and CTE estimates to provide a new set of results from a global economy-wide model that attempts to quantify the impacts on global markets, net farm incomes and welfare of the reforms since the early 1980s and of the policies still in place as of 2004. The chapter concludes by drawing on the lessons learned to speculate on the prospects for further reducing the disarray in world agricultural markets.